2017
DOI: 10.7150/thno.20041
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-194 Reverses HMGA2-driven Signatures in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the leading causes of cancer death worldwide with increasing incidence and mortality in developed countries. Oncogenes and microRNAs regulate key signaling pathways in CRC and are known to be deregulated. Oncogenic transcriptional regulator high-mobility group AT-hook 2 (HMGA2) participates in the transformation of several cancers including CRC and exhibits strong correlation with poor prognosis and distal metastasis. Evidence of HMGA2 and its co-regulated miRs contributing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 44 publications
1
28
0
1
Order By: Relevance
“…S6a). Unexpectedly, it was reported that HMGA2, an oncogene with pro-cancer stemness ability, interacted with miR-194 [28]. We found that HMGA2 negatively regulated miR-194-5p expression ( Fig.…”
Section: Exosomal Mir-194-5p Promotes Repair Of the Damaged Trcsmentioning
confidence: 54%
“…S6a). Unexpectedly, it was reported that HMGA2, an oncogene with pro-cancer stemness ability, interacted with miR-194 [28]. We found that HMGA2 negatively regulated miR-194-5p expression ( Fig.…”
Section: Exosomal Mir-194-5p Promotes Repair Of the Damaged Trcsmentioning
confidence: 54%
“…High-mobility group A2 (HMGA2) is a non-histone chromatin DNA-binding protein that modulates the transcription of several genes by binding to AT-rich sequences in the minor groove of B-form DNA and altering the chromatin structure [ 6 ]. It was demonstrated that overexpression of the HMGA2 protein occurs in various types of cancer, including CRC [ 7 ]. It was also shown that high expression of HMGA2 is related to tumor progression, a poor prognosis, and a poor response to therapy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…HMGA2 protein is highly expressed during embryonic development and is expressed at low levels in adult tissues (26,31). High expression of HMGA2 has been detected in most human malignancies, including colorectal cancer, Wilms' tumor and PDAC, and is associated with higher lymph node metastasis rates and poor tumor differentiation (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%